A replication of the relationship between elderly suicides rates and elderly dependency ratios: cross-national study - Shah, Ajit (Kermanshah University of Medical Sciences, 2010)
BACKGROUND: A positive correlation between elderly dependency ratios and elderly suicide rates has been observed using one-year cross-sectional data on elderly suicide rates. METHODS: A cross-national study designed to replicate this positive correlation between elderly dependency ratios and elderly suicide rates was undertaken by: (i) using one-year average of five years data on suicide rates; and (ii) using more recent data on both elderly suicide rates and elderly dependency ratios. Data on elderly suicide rates, and the total number of elderly and young people was ascertained from the World Health Organization website. RESULTS: The main findings were of significant positive correlations between elderly dependency ratios and suicide rates in both sexes in both the elderly age-bands (65-74 years and 75+ years). CONCLUSIONS: The replication of the positive correlations between elderly dependency ratios and elderly suicide rates by using one-year average of five years data on suicide rates suggests that this relationship is robust and accurate.